Tensile and flexural behaviour of LWAC members under short-term service loads. (1st June 2015) - Carmo, R.N.F.; Dias-da-Costa, D.
Highlights: An experimental study of LWAC members under tensile and flexural loading is presented. A new parameter is proposed for estimating deflections and cracks from steel stress. A procedure is proposed to quickly estimate crack widths in structural design. Design guidelines for LWAC members are assessed in terms of deformation and cracking. EC2 provides conservative estimates for cracking widths in the studied LWAC ties. Abstract: This paper presents a detailed study concerning the behaviour of Lightweight Aggregate Concrete (LWAC) members subjected to short-term tensile or flexural loading. For this purpose, a comprehensive experimental programme was carried out covering a wide range of LWAC specimens with different reinforcement ratios and classes of LWAC concrete, with compressive strength ranging from 40 MPa up to 70 MPa. The performance of Eurocode-2 (EC2) and Model Code (MC) guidelines were checked against experimental results, namely in what concerns deformation and cracking prediction for typical service stress levels. In the case of pure tensile loads, it was observed that MC adequately predicts the experimental deformations, whereas EC2 estimates are more adequate for higher reinforcement ratios. In the case of flexural loading, EC2 shows good agreement with experimental results. Furthermore, safe estimates were obtained when using EC2 to predict the crack widths in LWAC members under pure tensile load, whereas MC provided estimates in agreement with the experimental results. Finally, the paper addresses the viability of proposing a new parameter for quantifying deflections and cracking without relying on the tensile strength of concrete, thus avoiding the high variability of this experimental parameter.